KAJIAN USAHATANI PADI SAWAH DI DESA TOMBATU TIGA TIMUR KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - Anastasio A. J. Waleleng; Jenny ., Baroleh; Tommy F. Lolowang (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine farmer’s income of rice farming in Eastern Tombatu 3, Tombatu Village, Southeast Minahasa District. This Study take for March to May 2018. Primary data obtained from interview using questionnaires to 5 respondent based on Simplen Random Sampling method, because the respondent homogeneous. Data analyzed used income and cost analysiss, culculated using R/C Ratio. The result showed that the average income of the rice farmers in The Eastern Tombatu 3 Village Rp. 2,033,928 with an R/C Ratio 1,43. It means rice farming in Eastern Tombatu 3 Village Southeast Minahasa District profitable and worth the effort.*lwths*.